Quality Analysis of Banana –Oatmeal Energy Bar Enriched with Peanut Butter and Chocolate chips (Sahayaatra सहयात्रा, 2025)
The aim of this work was to prepare energy bar using ripe bananas, rolled oats, peanut butter and chocolate chips and evaluate its quality. Response Surface Methodology (RSM) with a randomized mixture design was used to create different formulations using Design Expert 13.1.5 software and 14 formulations were obtained. Formulated samples were subjected for sensory evaluations using 9 points hedonic rating scale. Based on the sensory evaluation, the results indicated that formulations with higher proportions of chocolate chips and peanut butter sample G and L were preferred. Physical properties of energy bar were measured, the addition of peanut butter and chocolate chips influenced the volume, texture and density of the bars. Potassium, calcium and radical scavenging activity were found significantly increased. Data from sensory analysis, physical properties and mineral were statistically analyzed and means were compared at 5% level of significance.